1979
DOI: 10.1055/s-0028-1092697
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Maternal Somatostatin Administration on Fetal Brain Cell Proliferation and its Relationship to Serum Growth Hormone and Brain Trophin Activity

Abstract: The effect of maternal somatostatin administration from days 14 to 20 of gestation was examined. Fetal body growth was unchanged but brain cell DNA synthesis per gram of tissue decreased. Maternal serum levels of growth hormone and brain trophin were elevated following treatment conclusion. It was suggested that this was a rebound phenomenon and that short term blockade of pituitary growth hormone release during somatostatin treatment had impaired fetal brain cell DNA synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…These hormones modulate cell division. Although most of the effects described have been in the postembryonic brain or in cell cultures, some data demonstrated or implied that maternal hormones, as well as embryonic growth factors, acting synergistically with endogenous opioids, might affect cell division in the embryonic brain (Sara et al . 1979; Balk et al .…”
Section: Discussionmentioning
confidence: 99%
“…These hormones modulate cell division. Although most of the effects described have been in the postembryonic brain or in cell cultures, some data demonstrated or implied that maternal hormones, as well as embryonic growth factors, acting synergistically with endogenous opioids, might affect cell division in the embryonic brain (Sara et al . 1979; Balk et al .…”
Section: Discussionmentioning
confidence: 99%
“…Fetal brain development: Several reports in the rat have raised the notion that maternally administered GH influences morphological and functional development of the fetal brain (345)(346)(347)(348)(349). However, fetal GH concentrations are undetectable after fetal decapitation (350), and by analogy to other species, it seems unlikely that GH can cross the rat placenta.…”
Section: Other Possible Actions Of Gh In the Fetusmentioning
confidence: 99%
“…However, GH may play a role in neu ronal proliferation during the fetal period [20] and/or placental growth [8], Recently it was demonstrated that maternal SS adminis tration decreased brain cell DNA synthesis [21] , Therefore, the low brain SS levels dur ing the fetal period will not only help main tain high circulating GH levels, but will have little or no influence on brain cell DNA syn thesis, at a time when neuronal proliferation is occurring rapidly.…”
Section: Discussionmentioning
confidence: 99%